Radiologic anatomy of the round window relevant to cochlear implantation and inner ear drug delivery. Issue 1 (1st January 2021) - Nguy, Peter L.; Saidha, Sheela; Jay, Ann; Jeffrey Kim, H.; Hoa, Michael
Abstract : Objective: To determine anatomic relationships and variation of the round window membrane to bony surgical landmarks on computed tomography. Study design: Retrospective imaging review. Methods: 100 temporal bone images were evaluated. Direct measurements were obtained for membrane position. Vector distances and angulation from umbo and bony annulus were calculated from image viewer software coordinates. Results: The angle of round window membrane at junction with cochlear basal turn was (42.1 ± 8.6)°. The membrane's position relative to plane of the facial nerve through facial recess was (14.7 ± 5.2)° posterior from a reference line drawn through facial recess to carotid canal. Regarding transtympanic drug delivery, the round window membrane was directed 4.1 mm superiorly from the inferior annulus and 5.4 mm anteriorly from the posterior annulus. The round window membrane on average was angled superiorly from the inferior annulus (77.1 ± 27.9)° and slightly anteriorly from the posterior annulus (19.1 ± 11.1°). The mean distance of round window membrane from umbo was 4 mm and posteriorly rotated 30° clockwise from a perpendicular drawn from umbo to inferior annulus towards posterior annulus. Together, these measurements approximate the round window membrane in the tympanic membrane's posteroinferior quadrant. Conclusions: These radiologic measurements demonstrate normal variations seen in round window anatomy relative to facial recess approach and bony tympanic annulus, providing a baseline to assess round window insertion for cochlear implantation and outlines anatomic factors affecting transtympanic drug delivery.